Determining the potential drivers of invasive C4 grasses at De Hoop Nature Reserve, South Africa - Munyai, Nthabeliseni Meryling (Department of Biological Sciences, 2019)
Grassland and shrubland distribution in SA is associated with rainfall seasonality. In grassland the vegetation is exclusively C4 while the shrub and tree component is generally C3. Shrublands, in contrast, are predominantly C3, for both woody and herbaceous species, though there can be a small C4 sedge and grass component. The C4 grassy biomes dominate the warm season rainfall region while C3 grasses predominate in the shrublands of the cool season rainfall regions. The C4 grasses are poorly competitive in cold climates. There are however anomalous patches of C4 grasses in cool season rainfall regions dominated by fynbos shrublands such as those at Potberg, De Hoop Nature Reserve, Overberg region, South Africa. Although the southern Overberg region receives rainfall year-round, more than half of the rain falls in the cooler months of the year. These C4 grassland patches appear to be invading the fynbos even on the nutrient poor podsols. The main objective of this study was to gain a better understanding of the ecology of these anomalous C4 grasslands in a fynbosdominated region. I first explored the role of roads as a conduit for grass invasion by sampling sites adjacent to and further away from the road verge. This was done by identifying all species in plots 5 m (Roadside pots) and 100 m (Adjacent plots) from the road verge every 500 m along a 14 km management road at Potberg. My results show that the most common C4 grasses were Cynodon dactylon and Eragrostis curvula whilst the most common C3 grass was Merxmuellera disticha. Both Roadside and Adjacent plots had more C4 grass species than C3 grasses. The frequency distribution of both C3 and C4 grass species was significantly higher on the Roadside plots than on the Adjacent plots. Although there was a higher incidence of C4 grass occurrence on the Roadside plots I conclude that, roadsides are not the conduit for C4 grass invasion into fynbos as several large patches of the C4 grass Eragrostis curvula and Imperata cylindrica can be found several kilometres away from the roadside and there are fewer C4 grasses away from the road verge. I then explored the impacts of C4 grasses on fynbos species diversity by identifying all the plants in 100 plots, half in fynbos-dominated vegetation and half in grassy patches. My results show that C4 grasses had a negative effect on fynbos species richness. The areas invaded by the C4 grass had fewer fynbos species (average of 7) compared to areas with C3 grasses (average 17). Some C4 grasses had more of an effect than others with some of the most aggressive the clonally spreading species Imperata cylindrica, Setaria sphacelata var. torta and Cynodon dactylon. C4 grasses such as Aristida diffusa and Themeda triandra occur naturally in the fynbos with little impact on fynbos species richness. Eragrostis curvula, a tall bunch grass, was also locally dominant in places at the expense of fynbos species diversity. To examine the drivers influencing colonisation of fynbos by C4 grass, I set up a transplant experiment designed to examine the extent to which topographic position along a slope (moisture availability), an increase in nutrient availability and a decrease in competition for resources influences the establishment and growth of C4 grass. To do this I transplanted tufts of Setaria sphacelata var. torta in three positions along a slope, with and without nutrient additions and with and without competition for soil resources. I removed competition for resources by trenching and inserting a plastic sheath around each grass tuft to a depth of 500 mm. My results show an increase in mortality in drier treatments at the top of the slope. Trenching and fertiliser addition had significant positive effects on grass biomass and negative effects on root shoot ratios. Slope position however only had significant effects on root shoot ratios. Plants at the top of the slope had significantly higher root/shoot ratios than those plants at the bottom (P<0.05). Trenching did not have a significant effect on root shoot ratios (P>0.05). Based on the results of this research, it can be concluded that the grass patches have a negative effect on fynbos species diversity. These grass patches are not a remnant from when the reserve was still a farm but are relatively new and are not invading out from the roads. I examined rainfall seasonality from 1910 to 2015 and found no change. My results from trenching show that physical disturbance that breaks up fynbos root systems will help promote C4 grass invasion. Thus, any activities that increases physical disturbance of the fynbos such as off-road vehicles and trampling by large mammals must be avoided to maintain intact fynbos. While this has not occurred at Potberg, I speculate that because of fire suppression, there has been a decline in species diversity and a reduction in competition for resources allowing the C4 grasses to establish and dominate. The impact of fire on C4 grass needs more research, to understand if too frequent or less frequent fire will disturb fynbos and allow invasion by C4 grasses.